Environmental Policy Space in Bangladesh’s Bilateral Investment Treaties (Dhaka University Law Journal, 2025)
This article delves into the intricate relationship between International Investment Agreements (IIAs) and environmental policies in Bangladesh. While the government endeavors to attract increased FDI to bolster competitiveness in national market, Bangladesh struggles with the adverse impacts of climate change and environmental degradation, affecting communities across the nation. This juxtaposition underscores the pressing need to address the ongoing global debate surrounding the interplay of environment and investment, particularly in light of contemporary challenges. Recognizing the evolving nature of both the natural environment and regulatory frameworks, the article advocates for a balanced and foreseeable investment regime for foreign investors, crucial for climate-vulnerable countries like Bangladesh. To evaluate the eficacy of IIA regime in addressing these concerns, the study conducts a meticulous analysis of 30 Bilateral Investment Treaties (BITs) signed by Bangladesh. Two central inquiries guide this assessment: first, the potential impact of the BIT regime on states’ regulatory space, particularly in environmental matters, and second, the necessity of revising the existing BIT regime. Employing qualitative research methodologies, the article synthesizes diverse primary and secondary sources, conducting thorough analyses of both Bangladeshi BITs and global trends in investment agreements. Findings underscore the antiquated nature of Bangladesh’s current BIT regime, highlighting its potential to constrain policy space in environmental sectors. Recommendations are made for revisiting the BIT regime, aligning it with contemporary global concerns and aspirations for sustainable development.Dhaka University Law Journal Vol.35, Issue.2, December 2024 P. 191-222